Thermal Cycles and Residual Stresses in FSW of Aluminum Alloys: Experimental Measurements and Numerical Models - Buglioni, Luciano (2015)
In the present work longitudinal residual stresses obtained by different methods, numerical and experimental, in Friction Stir Welding (FSW) process for AA7075 were analyzed. The experimental method employed for residual stresses measurements was sectioning, whereas the numerical is a finite element (FEM) thermomechanical coupled model which does not consider the stir in the material. The effect of travel speed during FSW was also analyzed, measuring with strain gages positioned in several points at different distances from weld centerline. From the obtained residual strains, the stress values, stress variation against weld centerline distance and null stress point were calculated. Numerical and experimental stress values agree in order of magnitude, being greater in numerical method inside stir zone's edge and even outside, and smaller at some point towards the end of plate. Stress variation against weld centerline distance and null stress position vary in different ways for each method. This phenomenon agrees with another works, and it could be related with no consideration of the stir process in the numerical method. Thus, it has been developed a simplified finite element model which averages in magnitude experimental residual stress in FSW.